Information organization via computational thinking: case study in a primary school classroom - Cavalheiro, Simone A. C.; Pernas, Ana M.; de Aguiar, Marilton S.; Foss, Luciana; Du Bois, André; Reiser, Renata H. S.; Piana, Clause de Brum; Weisshahn, Yuri (Anais do Workshop sobre Educação em Computação (WEI); 2016: Anais do XXIV Workshop sobre Educação em ComputaçãoDO - 10.5753/wei.2016.9661, 2016)
Technological innovations have changed the profile of professionals required by economy sectors demanding skills related to problem solving and logical reasoning. Concurrently with this reality, Computational Thinking emerges as a methodology for solving problems, which is able to develop many of these skills. This article reports the experience in applying the activities referred as Binary Numbers, Color by Numbers, Sorting Algorithms and Battleships, which aims at developing some of necessary skills for the practice of Computational Thinking by fourth-graders. The article resumes the activities, and evaluates the obtained results.